Combustion Characteristics of Biodiesel Droplets from Nyamplung Seeds with Eggshell Catalyst Using PLX-DAQ Software - Sukma, Kinanti Wilujeng; Sanata, Andi; Jatisukamto, Gaguk; Kustanto, Nurkoyim; Darsin, Mahros (Jurnal Teknologi Informasi dan Pendidikan, 2025)
The purpose of this study was to determine the effect of eggshell catalyst (CaO) on the combustion characteristics of nyamplung oil biodiesel droplets (Calophyllum inophyllum L) on flame visualization, ignition delay, and temperature. At present, Indonesia still uses fossil fuels, namely diesel. However, over time there are alternative fuels using palm oil raw materials. However, palm oil is also used as a source of food so that it will have an impact on the scarcity of palm oil. In this study, we looked for alternative energy using nyamplung seeds (Calophyllum inophyllum L.) with catalyst weight variations of 1%, 3% and 5%. The tested droplet volume of 1 ml was placed in a type K thermocouple. The results of this study showed that the percentage of catalyst weight increased temperature and shortened ignition delay. The highest temperature and lowest ignition delay were found at a variation of 5% with the highest temperature of 679.5 °C and ignition delay of 3000 ms.